Using ultrashort xuv laser pulses to investigate symmetry breaking in one-photon single-ionization of H2 (2009)
ABSTRACT: We have evaluated photoelectron angular distributions from xed-in-space molecular hydrogen exposed to ultrashort xuv laser pulses. The theoretical method is based on the solution of the time-dependent Schrodinger equation in a basis of stationary states that include all electronic and vibrational degrees of freedom. We conclude that the origin of the asymmetry in these angular distributions is the interference of the two dissociative ionization channels (1s(sigma)g and 2p(sigma)u) due to delayed ionization from the H2 doubly excited states.